Long term thinning and logging in Australian cypress pine forest: Changes in habitat attributes and response of fauna. (June 2015) - Eyre, Teresa J.; Ferguson, Daniel J.; Kennedy, Michael; Rowland, Jesse; Maron, Martine
Highlights: Thinning and logging, separately and in combination, influence faunal patterns. Response of various functional groups of species was mixed. Thinning and logging influence key habitat features; small trees and large trees. Thinning affects fauna as much as selective logging. Forest with minimal thinning and logging management history must be conserved. Abstract: The manipulation of habitat through thinning and logging activities may have cascading effects on fauna because of direct and indirect changes to key habitat features. However, the combined effect of thinning and logging on fauna has not been investigated for Australian forests, despite the widespread use of thinning as a silvicultural management tool in selectively logged forests, and the emerging interest in thinning for biofuels. We therefore surveyed reptiles, birds and key habitat variables at sites selected to sample four management classes reflecting categories of thinning and/or logging activity in cypress pine Callitris glaucophylla forests of the Brigalow Belt bioregion of Australia. Habitat structure and assemblages of reptile and bird species were distinct across the four management classes, reflecting long-term cumulative impacts of small- and/or large-diameter tree removal in a dynamic system, but the response of various functional groups of species was mixed. Recovery of some habitat elements (e.g. small trees) to a state that maintains densities of most fauna species appears to be relatively rapid, but depends on the combined effect of thinning and logging. Other habitat elements, such as large cypress trees which were reduced by logging and unaffected by thinning, require longer time frames to mature and therefore will be critical resources to maintain during future management activities in cypress forests. Overall, it appears that thinning activities affect fauna and therefore must be considered when making decisions about forest management. We suggest management of production forests aims for a mosaic of thinning and/or logging combinations across the landscape, but emphasise the importance of retaining or restoring unthinned and unlogged areas.